O processo de sucessão em empresa familiar: levantando véus sobre as relações interpessoais - Moreira, Michelle Oliveira Menezes (2009)
The motivation for the implementation of this work was the interest in the topic of family business management, in particular the process of succession. In Brazil, there is the issue of family business management is poorly studied, there is even a lack of